MODEL PREDIKSI INDIKATOR KEBERLANJUTAN SUMBERDAYA AGROINDUSTRI TERI NASI KERING MENGGUNAKAN SISTEM DINAMIK - Bambang Herry; P Machfud; Aji Hermawan; Eko S Wiyono (AGROINTEK, 2011)
Chirimenagroindustries facingseriousproblemsfrom theaspectof resourceswhichcanthreatensustainabilityin the future. This studyaimstopredictthe value ofresourcesustainabilityindicator of chirimen agroindustriesincoastal area ofTuban, LamonganandGresikusingdynamicsystemmodelsanddetermine thestatus oflong-term sustainabilityof resourceusing multidimensional scaling (MDS) techniques. The results ofthe modelpredictionsindicatethat thevalue ofthe resourceindicators chirimen agroindustrialfor thenext 5 yearshave averylowvalueand includedin the categoryare notsustainable. Policy scenariosthat couldincrease the valueof indicators andsustainabilityis a policy thatsynergizecapture effort that appropriatewith maximum sustainable yield (MSY), increasedabsorptionof rawmaterialsfromthe regionto 100% and improved work in processmaterialsto 10%.